An investigation of the effect of texting on hazard perception using fuzzy signal detection theory (fSDT). (October 2018) - Burge, Rondell; Chaparro, Alex
Highlights: The relevance of Fuzzy Signal detection for studying hazard perception is proposed. Fuzzy Signal detection was used to study how texting effects a driver's response to hazards. Texting reduced the identification and likelihood of responding to hazards. Texting influences both a drivers' sensitivity (d′) and criterion (beta). Shifts in d′ and beta are moderated by cognitive load and by the driving context. Abstract: Hazard perception is a multi-faceted process that requires drivers to maintain awareness of a complex driving environment. Most research studies, however, utilize behavioral responses to a small number of discrete hazardous events (e.g., response to a braking lead vehicle, vehicle lane deviations, or pedestrians) to assess a driver's hazard perception ability. The purpose of this study was to explore how performing a texting task impacts a driver's hazard perception ability while viewing real-world driving scenes using f SDT metrics. The results showed that texting increased perceived mental workload and reduced the participants' ability to discriminate hazards and reduced their likelihood of responding to a hazard. The results highlight changes in the hazard perception process, suggesting that distraction causes both a loss in sensitivity and a shift in response bias. Additionally, the results indicate that these shifts are at least in part, moderated by changes in cognitive load due to the secondary task and the current driving environment. These results also highlight the complexity in which distraction can impact both the allocation of cognitive resources as well as attentional selection.